SPINDLE OF SUPERNATURAL EXPERIENCES - SAAJAN KURIAN MATHEW: अलौकिक अनुभवों का चितेरा - साजन कुरियन मैथ्यू - abraham, Adlin (International Journal of Research -GRANTHAALAYAH, 2014)
Colorist artist Sajan Kurian Mathew got the opportunity to write an art travelogue. Early paintings of Sajan Kurien Mathew include Raja Ravi Varma, Western artists Delacra, Michael Carrivagio Angelo, Salvador Dali, Wistler, etc. Influenced by the genre, there was an orthodox and surrealist depiction. His oil paintings based on the life of Jesus (which is presently beautiful in the churches of Jabalpur, Kerala, Sihora, Shahdol, and Delhi,) using colors very closely in human organ design, background, environment etc. Has recorded the evidence. If the artist is not satisfied in presenting these artifacts in this form, then the entire canvas was erased and then he was not satisfied, yet he was not satisfied, and then he worked hard to create a masterpiece, which is such a work which the artist has given Completely erased and then rebuilt. is. In his paintings, the viewer becomes aware of all those emotions and finds the ideological duality that arises in his inner self. That is to say, the artist's color scheme, the paintbrush, has been completely successful in evoking the ambitions. रंगों से खेलने वाले कलाकार साजन कुरियन मैथ्यू क¨ रंगों की कला यात्रा लिखने का सुअवसर प्राप्त हुआ।साजन कुरियन मैथ्यू के प्रारम्भिक दौर के चित्रों में राजा रवि वर्मा, पाश्चात्य कलाकार डेलाक्रा, माइकल कैरीवैग्यो एंजेलो, सल्वाडोर डाली, विस्टलर, आदि यूरोपीय चित्रकारों की शैली से प्रभावित होकर यर्थाथवादी और अतियर्थाथवादी चित्रण हुआ। ईसा के जीवन पर आधारित उनके तैल चित्र (जो वर्तमान में जबलपुर, केरल, सिहोरा, शहडोल,और दिल्ली, के गिरजाघरों में शोभायमान हंै,) मंे मानवीय अंग विन्यास, पृष्ठ भूमि, वातावरण आदि में अत्यधिक बारीकी से रंगो का प्रयोग कर वास्तविकता का साक्ष्य अंकित किया है। इन कलाकृतियों को इस रूप विधान में प्रस्तुत करने में कलाकार ने संतुष्ट न होने पर पूरा का पूरा कैनवास मिटा डाला फिर बनाया इसके बावजूद वे संतुष्ट नहीं हुये तो फिर जी जान से मेहनत कर पुनः कृति का सृजन किया ऐसे ही कृति है जिसे कलाकार ने दो बार पूरा-पूरा बनाकर मिटाया और फिर बनाया। है। इनके चित्रों में दर्शक उन सभी भावों से रूबरू हो जाता है और स्वयं के अन्तर्मन में उठने वाले वैचारिक द्वन्द को पाता है। कहने का तात्पर्य यह, कि कलाकार की रंगयोजना, तूलिका घात - भावों को उकेरने में पूर्णतः सफल हुई है।